Pengaruh Helicopter parenting Terhadap Perkembangan Sosial dan Percaya Diri Anak PAUD - Yanti, Lisfa; Mahyuddin, Nenny (Aulad: Journal on Early Childhood, 2023)
The background of this research is that children experience a level of difficulty in regulating emotions and confidence in doing something that is caused by overprotective parenting (too controlling). The purpose of this study was to determine the effect of helicopter parenting on children's social development and self-confidence at PAUD Ar-Rasyid Payakumbuh. The research method used is this research uses a quantitative approach in the form of Pre-Experimental Design, with the One-Shot Case Study method. The research subjects were class B students of Ar-Rasyid Payakumbuh PAUD. The research instruments used were observation sheets, questionnaires, and documentation. The results of the study found that the t value of helicopter parenting and children's social development was 4.073 with a significance of 1.771 (p>0.05). This shows that there is a significant influence between helicopter parenting and the social development of children of PAUD Ar-Rasyid Payakumbuh. Furthermore, using the t-test, the results showed that helicopter parenting and children's self-confidence amounted to 6.440 with a significance of 1.771 (p>0.05). This shows that there is a significant influence between helicopter parenting and children's confidence in PAUD Ar-Rasyid Payakumbuh. It is recommended to future researchers to conduct research related to parenting on other variables